1997
DOI: 10.1021/ie9602771
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Protection of Mild Steel by a Calcite Layer

Abstract: Artificial calcite lining represents a novel technique for the rehabilitation of water mains. Calcite linings, similar to the commonly used cement-mortar linings, are of porous nature. The corrosion protection mechanisms of calcite linings were investigated by polarization techniques, complemented by scanning electron microscopy observations and energy dispersive spectrometry analyses. The effect of time on lining durability was examined by exposure of coated mild steel (1020) coupons in a controlled flowing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Several other additional geochemical factors can be important in inhibiting corrosion of Fe metal. These include the presence of dissolved silica (Amaral and Muller 1999), carbonate and bicarbonate (Sutcliffe et al 1972;Stiksma and Bradford 1985;Mao et al 1994;Keyser et al 1997;Al-Hassan et al 1998;Qiao et al 1998;Adamy and Cala 1999), and soluble organic materials (Malik 1995). The presence of dissolved silica promotes the formation of a hydrous gel-like Fe-Si film on the surface of the metal, which acts to enhance corrosion resistance (Amaral and Muller 1999).…”
Section: Could Feni Metal Grains Survive Asteroidal Parent Body Altementioning
confidence: 99%
See 1 more Smart Citation
“…Several other additional geochemical factors can be important in inhibiting corrosion of Fe metal. These include the presence of dissolved silica (Amaral and Muller 1999), carbonate and bicarbonate (Sutcliffe et al 1972;Stiksma and Bradford 1985;Mao et al 1994;Keyser et al 1997;Al-Hassan et al 1998;Qiao et al 1998;Adamy and Cala 1999), and soluble organic materials (Malik 1995). The presence of dissolved silica promotes the formation of a hydrous gel-like Fe-Si film on the surface of the metal, which acts to enhance corrosion resistance (Amaral and Muller 1999).…”
Section: Could Feni Metal Grains Survive Asteroidal Parent Body Altementioning
confidence: 99%
“…The presence of dissolved silica promotes the formation of a hydrous gel-like Fe-Si film on the surface of the metal, which acts to enhance corrosion resistance (Amaral and Muller 1999). Corrosion resistance is also facilitated by the occurrence of CO 2 , HCO − 3 , CO 2− 3 , which all contribute to the formation of FeCO 3(aq) bicarbonate (Sutcliffe et al 1972;Stiksma and Bradford 1985;Mao et al 1994;Malik 1995;Keyser et al 1997;Al-Hassan et al 1998;Qiao et al 1998;Adamy and Cala 1999). All of these constituents are available and certainly mobile in CM2 chondrites during aqueous alteration.…”
Section: Could Feni Metal Grains Survive Asteroidal Parent Body Altementioning
confidence: 99%
“…study has identified reduction of the pH in the cement paste pore solution due to the carbonation reaction as a major cause of the corrosion of steels in steel-reinforced concrete (7). Contrary to the adverse effects of carbonation on concrete, recent studies have found that carbonation of concrete increases the sequestration of hazardous waste, heavy metals, other inorganic pollutants, and even radioactive compounds (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Through the crossing point of the two extended cords from the straight‐line parts of the anode and cathode polarization curves, the corrosion potential, corrosion current density can be determined. Besides, the Tafel constants ba and bc of anode and cathode polarization curves separately reflect the process tendencies of anodic and cathodic reactions, and because of the linear correlation between the corrosion current density and the electrochemical corrosion rate, therefore the corrosion current density can be deemed as the symbol of the corrosiveness of sedimentary liquids to the steel coupons . The anode and cathode polarization curves with respect to the Q235 and 16MnR steel coupons steeped in the sedimentary liquid from hydro‐stabilizing feed oil are shown in Figure , and Table presents the relevant electrochemical parameters.…”
Section: Resultsmentioning
confidence: 99%